EDUCATORS’ FEEDBACK ON WEBSITE “OVERCOMING STRESS AND ANXIETY TOGETHER: TEACHERS – SCHOOLCHILDREN – PARENTS” - Kaupuzs, Aivars; Malykhin, Oleksandr; Aristova, Nataliia; Kalvans, Eriks; Orska, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The research aim was to collect feedback from educators on the website “Overcoming Stress and Anxiety Together: Teachers – Schoolchildren – Parents” created within the joint Latvian-Ukrainian project “Web-based Support System for Educators to Reduce Children’s Anxiety in War-affected Areas” (Registration No GPK-07/2022). Immediately after creating a demo version of the website, researchers organised webinars aimed at presenting its content to educators in Ukraine and collected feedback from webinars’ participants. For that very reason the joint Latvian-Ukrainian team of researchers developed a web-based questionnaire using Google Forms. The population of the conducted research comprised 216 educators from different regions of Ukraine including university lecturers, general secondary teachers, researchers and students of pedagogical specialties. The obtained results proved the necessity of developing the web-based support system for educators aimed at reducing anxiety among schoolchildren in war-affected areas in Ukraine.